Bone mineral density in adult coeliac disease: An updated review - Alfredo J. Lucendo; Alvaro García-Manzanares (Revista Espanola de Enfermedades Digestivas, 2013)
Introduction and objectives: coeliac disease (CD) affects around 1-2 % of the world population. Most patients are now diagnosed when adults, suffering the consequences of an impaired bone mineralization. This review aims to provide an updated discussion on the relationship between low bone mineral density (BMD), osteopenia and osteoporosis, and CD. Methods: a PubMed search restricted to the last 15 years was conducted. Sources cited in the results were also reviewed to identify potential sources of information. Results: low BMD affects up to 75 % of celiac patients, and can be found at any age, independently of positive serological markers and presence of digestive symptoms. The prevalence of CD among osteoporotic patients is also significantly increased. Two theories try to explain this origin of low BMD: Micronutrients malabsorption (including calcium and vitamin D) determined by villous atrophy has been related to secondary hyperparathyroidism and incapacity to achieve the potential bone mass peak; chronic inflammation was also related with RANKL secretion, osteoclasts activation and increased bone resorption. As a consequence, celiac patients have a risk for bone fractures that exceed 40 % that of matched non-affected population. Treatment of low BMD in CD comprises gluten-free diet, calcium and vitamin D supplementation, and biphosphonates, although its effects on CD have not been specifically assessed. Conclusions: up to 75 % of celiac patients and 40 % of that diagnosed in adulthood present a low BMD and a variable increase in the risk of bone fractures. Epidemiological changes in CD make bone density scans more relevant for adult coeliacs.